2014
DOI: 10.1021/cb500371g
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Modulation of Src-Family Kinase Regulatory Interactions with ATP-Competitive Inhibitors

Abstract: Multidomain protein kinases, central controllers of signal transduction, use regulatory domains to modulate catalytic activity in a complex cellular environment. Additionally, these domains regulate noncatalytic functions, including cellular localization and protein–protein interactions. Src-family kinases (SFKs) are promising therapeutic targets for a number of diseases and are an excellent model for studying the regulation of multidomain kinases. Here, we demonstrate that the regulatory domains of the SFKs S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 60 publications
4
66
0
Order By: Relevance
“…Thus by intercepting a particular conformer, a small molecule could have either a positive or a negative influence on the binary and ternary transcription factor–coactivator assembly process. Certainly the field can be guided by the success seen in targeting particular conformational states of kinases or of the protein folding machinery for enhanced selectivity and context-specific effects on downstream processes 8,18,19 .…”
mentioning
confidence: 99%
“…Thus by intercepting a particular conformer, a small molecule could have either a positive or a negative influence on the binary and ternary transcription factor–coactivator assembly process. Certainly the field can be guided by the success seen in targeting particular conformational states of kinases or of the protein folding machinery for enhanced selectivity and context-specific effects on downstream processes 8,18,19 .…”
mentioning
confidence: 99%
“… 9 , 10 In fact, our lab has shown that ATP-competitive ligands that stabilize Src and Hck in an inactive αC helix-out conformation strengthen intramolecular SH3/SH2 domain engagement upon binding. 12 , 18 In contrast, inhibitors that stabilize helix αC in an active conformation weaken interactions between the SH2/SH3 domains and their respective intramolecular ligands. While the basic allosteric regulatory network between the catalytic and regulatory domains of SFKs is well-characterized, less is known about how SH2-CD linker heterogeneity affects the magnitude of this bidirectional relationship.…”
mentioning
confidence: 99%
“…Inhibitor 1 contains an extended 4-phenoxyphenyl substituent at the C-3 position on the pyrazolopyrimidine scaffold that occupies a hydrophobic pocket created by the outward movement of helix aC (Figure 2A, left). 14,[18][19]31 Inhibitor 2 stabilizes the DFG-out inactive conformation of tyrosine kinases (Figure 2A, right). Inhibitor 2 contains a 3-trifluoromethylbenzamide substituent that occupies the hydrophobic pocket formed by the displacement of the DFG-motif.…”
Section: Results and Discussion Inhibitors Divergently Modulate The Gmentioning
confidence: 99%
“…While inhibitors that stabilizes the DFG-out inactive conformation promote an open global conformation of tyrosine kinases that contain an SH3-SH2-CD architecture, 22,23 we have found that other classes of ATPcompetitive inhibitors are also capable of promoting allosteric disengagement of regulatory SH2 and SH3 domains. 18 To better understand the common features of inhibitors that promote an open global conformation of the SH3-SH2-CD regulatory module, we assembled a panel of 13 inhibitors that contain structurally diversified substituents that make varied ATP-binding site contacts and tested them in biochemical assays for the global conformational state of Src ( Figure 3A). Inhibitors 1, 3, and 4 contain pharmacophores that should stabilize the helix aC-out inactive conformation of Src, 14, 17 while 2 and 5 contain substituents that stabilize the DFG-out form.…”
Section: Results and Discussion Inhibitors Divergently Modulate The Gmentioning
confidence: 99%
See 1 more Smart Citation